Cognitive styles within an exploratory search system for digital libraries. Issue 6 (7th October 2014) - Peter Willett, Professor; Goodale, Paula; David Clough, Paul; Fernando, Samuel; Ford, Nigel; Stevenson, Mark
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the effects of cognitive style on navigating a large digital library of cultural heritage information; specifically, the paper focus on the wholist/analytic dimension as experienced in the field of educational informatics. The hypothesis is that wholist and analytic users have characteristically different approaches when they explore, search and interact with digital libraries, which may have implications for system design. Design/methodology/approach – A detailed interactive IR evaluation of a large cultural heritage digital library was undertaken, along with the Riding CSA test. Participants carried out a range of information tasks, and the authors analysed their task performance, interactions and attitudes. Findings – The hypothesis on the differences in performance and behaviour between wholist and analytic users is supported. However, the authors also find that user attitudes towards the system are opposite to expectations and that users give positive feedback for functionality that supports activities in which they are cognitively weaker. Research limitations/implications – There is scope for testing results in a larger scale study, and/or with different systems. In particular, the findings on user attitudes warrant further investigation. Practical implications – Findings on user attitudes suggest that systems which support areas of weakness in users' cognitive abilities are valued, indicating an opportunity to offer diverse functionality to support different cognitive weaknesses. Originality/value – A model is proposed suggesting a converse relationship between behaviour and attitudes; to support individual users displaying search/navigation behaviour mapped onto the strengths of their cognitive style, but placing greater value on interface features that support aspects in which they are weaker.